PENERAPAN PENDEKATAN MATEMATIKA REALISTIK TERHADAP PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Kiki Zakiyah; Uba Umbara; Muhammad Irfan Habibi (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2016)
The study involved an experimental class and control class is taken from the 9th grade at SMP Negeri 4 Brass. Studies conducted using essay test instruments for evaluating mathematical problem-solving ability and a questionnaire to determine the students' response to realistic mathematics approach. The discovery in this research is the mathematical problem solving ability of students who received study of mathematics by realistic mathematics approach better than students who received conventional learning, improvement of mathematical problem solving ability experimental class in middle category and the students' response to the positive realistic mathematics learning.